Frontal plane hip joint loading according to pain severity in people with hip osteoarthritis. Issue 6 (19th December 2017) - Hall, Michelle; Allison, Kim; Wrigley, Tim V.; Metcalf, Ben R.; Pua, Yong‐Hao; Van Ginckel, Ans; Bennell, Kim L.
ABSTRACT: The primary objective was to examine the hip adduction moment during walking in people with hip osteoarthritis (OA) according to pain severity. Sixty‐eight participants with unilateral symptomatic hip OA were included. Pain during walking was assessed on a 5‐point Likert item within the Western Ontario and McMaster Universities Index (no pain = 12; mild pain n = 37; moderate pain n = 19). Measures of the external hip adduction moment (peaks, Nm/BW × BH (%) and impulse, Nm.s/BW × BH (%)) were determined. Other measures included frontal plane hip, pelvis and trunk kinematics, walking speed and peak isometric hip abductor strength. Variables were compared according to pain severity using linear models and biomechanical variables were examined. Participants with moderate pain had a significantly higher second peak hip adduction moment and impulse compared to those with less pain. There was no difference in any measure of hip adduction moment between those with mild pain and no pain. There were no differences in kinematics across pain severity categories. Participants with moderate pain had a significantly slower walking speed compared to participants with mild and no pain. Participants with moderate pain had weaker peak isometric hip abductor strength compared to those with mild pain and no pain. The hip adduction moment during walking, hip abduction strength and walking speed differs according to pain severity during walking in people with hip OA. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1637–1644, 2018.